Avaliação de técnicas de colorimetria para quantificação de concentração aplicadas à engenharia química - Boff, Eduardo Cesar (2021)
Colorimetric techniques have shown great development in recent decades due to the miniaturization of instruments and the expansion of programming languages. Different systems have been proposed to correlate some physical quantity with color, increasing the possibility of new techniques over those already existing in certain situations. This work proposes the application of the gray scale mathematical model and another derived from it for correlation with the concentration of different solutions with colored analytes. Several colors were evaluated in the RGB system by a color sensor compatible with Arduino, by a cell phone camera, and by a webcam associated with an algorithm in the Python programming language. All correlations were compared with UV-VIS spectrophotometry, with the standard deviations, advantages, disadvantages, and limitations of each one. Considering the color and model with the best experimental correlation, it was used for the analysis of determination of residence time (DTR) in CSTR and PFR reactors at two different flow rates, and also compared with UV-VIS spectrophotometry. For grayscale adjustments, each color in each methodology presented a necessary correlation. For the proposed model, all colors were able to be represented, considering the evaluated concentration range. For DTR, assessed both by UV-VIS spectrophotometry and by the best fit model for tracer color, it is concluded that the reactors showed dead volume, even with significant differences between the time calculated by both methodologies.